MANAGERIAL AND PROFESSIONAL JUDGEMENT IN GENERAL INSURANCE RESERVING - Buame-Leyawor, Eugene Kofi (2005)
The demise recently of notable blue chip insurance companies and recent investigations of American International Group Inc (AIG) brings to the fore the relevance of using managerial judgement in the preparation of financial statements of insurance companies. This paper investigates the use of managerial and professional judgement in estimating required claims or technical reserves that are adequate to meet policyholders obligations in general insurance companies. The motivations influencing the assumptions on which managerial judgement is based are analysed.